2022
DOI: 10.2174/1871527320666210122092330
|View full text |Cite
|
Sign up to set email alerts
|

Neurokinin-1 Receptor Antagonist Reverses Functional CNS Alteration Caused by Combined γ-rays and Carbon Nuclei Irradiation

Abstract: Background: Ionizing Radiation (IR) is one of the major limiting factors for human deep-space missions. Preventing IR-induced cognitive alterations in astronauts is a critical success factor. It has been shown that cognitive alterations in rodents can be inferred by alterations of a psycho- emotional balance, primarily an anxiogenic effect of IR. In our recent work, we hypothesized that the neurokinin-1 (NK1) receptor might be instrumental for such alterations. Objective: The NK1 receptor antagonist rolapita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 76 publications
1
10
0
Order By: Relevance
“…On the one hand, rapid habituation correlates positively with OEB [ 91 , 92 ] and adaptive, nonpathological anxiety [ 93 ], which fully corresponds to the emotional status of animals irradiated at space-related doses. The direction of this correlation is also confirmed in the study, which showed the absence of irradiation effects on habituation against the background of anxiolytic therapy [ 82 ]. On the other hand, in both humans and animals, the disruption of habituation is strongly correlated with cognitive impairments [ 94 , 95 ] and vice versa [ 93 , 96 ].…”
Section: Mental Health and Ionizing Radiationsupporting
confidence: 53%
See 2 more Smart Citations
“…On the one hand, rapid habituation correlates positively with OEB [ 91 , 92 ] and adaptive, nonpathological anxiety [ 93 ], which fully corresponds to the emotional status of animals irradiated at space-related doses. The direction of this correlation is also confirmed in the study, which showed the absence of irradiation effects on habituation against the background of anxiolytic therapy [ 82 ]. On the other hand, in both humans and animals, the disruption of habituation is strongly correlated with cognitive impairments [ 94 , 95 ] and vice versa [ 93 , 96 ].…”
Section: Mental Health and Ionizing Radiationsupporting
confidence: 53%
“…Recently, the involvement of the neurokinin-1 receptor in the IR-induced anxiogenic effect has been confirmed pharmacologically. At the same time, downregulation of 5-HT 2c serotonin receptor expression in the amygdala as well 5-HT 4 in the hypothalamus can be considered as a neuro-adaptive anxiolytically-orientated response of nerve tissue [ 82 ]. Thereby, due to the anti-anxiety molecular changes, the anxiogenic effect of irradiation is probably not persistent.…”
Section: Mental Health and Ionizing Radiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Since rats exhibit increased anxiety‐like behaviour after exposure to repeated withdrawal episodes we hypothesized that the effectiveness of rolapitant treatment in reducing alcohol intake following withdrawal may be due to its anxiolytic activity. Indeed, NK1r antagonists have been found to exert anxiolytic‐like effects [20], although less pronounced than those reported for benzodiazepines [21]. It is well known that chronic alcohol consumption increases stress reactivity [22,23] and promotes anxiety disorders [24], which, in turn, contributes to the maintenance of and relapse to pathological alcohol use [25].…”
Section: Discussionmentioning
confidence: 99%
“…However, other mechanisms such as modulation of serotonergic and noradrenergic systems may also be involved in NK1‐mediated anxiolytic effects [32]. It has been found that rolapitant reduces the monoaminergic‐dependent overactivation of the hypothalamic–pituitary–adrenal axis [21]. Another explanation of rolapitant’s effects on alcohol intake comes from a series of studies of NK1r antagonists as a promising medication for neuroinflammatory disease treatment [33].…”
Section: Discussionmentioning
confidence: 99%